Development of Computer Intelligent Control System Based on Modbus and WEB Technology - Ran, Longyi; Wu, Yenchun Jim (Bright Publisher, 2023)
With the increasing popularity of intelligent computer control systems in our country, the accuracy and efficiency of intelligent control in the current computer control systems have attracted more and more attention. Modbus and WEB technology have a simple chassis format, compact and powerful functions. On this basis, based on the current research status of intelligent computer control technology, this article analyzes the problem of optimizing intelligent computer control systems based on Modbus bus and WEB technology in the application process, and improves the intelligent computer control systems based on Modbus bus and WEB technology.